Odnos politike do znanja v družbi znanja - Kodelja, Zdenko (Šolsko polje, 2013)
In short paper, only certain aspects of the relationship of the EU and Slovenia to knowledge society - which is defined as a knowledge society in strategic political documents - are discussed. The relationship is instrumental: knowledge has value primarily because it is seen as a means of achieving economic growth and improving the competitiveness of the European and Slovenian economies. On the other hand, the attitude of politicians and knowledge-based society is - if it is judged according to their position on investment in research and development - ambiguous: some act in accordance with what they say, while others, on the contrary, say one thing, but do another.
Keywords: družba znanja; knowledge; knowledge-based society; politika; knowledge society; znanje; vzgoja in izobraževanje; politics; education